Towards A Resilent Society Through Social Studies Intergredied Disaster Mitigation Education in Basic School Students - Pinkan Amita Tri Prasasti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: In developing countries, educating all segments of society about the threat of disaster is not always possible due to a lack of expertise and educational materials. Consequently, one of the best ways to disseminate disaster risk awareness programs is to integrate this initiative into children's activities through education. Important information for a large part of the population can be conveyed through the knowledge, skills and enthusiastic motivation of the children. The purpose of this study is to provide an educational picture to the wider community about the importance of disaster mitigation education which is internalized through education, especially social studies learning for elementary school children. Children as assets and future leaders, can learn to protect themselves and their environment in the future through a global mitigation culture to increase the safety of themselves, their families and their communities as they grow up. Children are seen as a 'powerful force' in behavior change for the next generation to deal with emergencies when they occur and bounce back from the effects of disasters.Abstrak: Di negara berkembang, mendidik semua lapisan masyarakat tentang ancaman bencana tidak selalu mungkin karena kurangnya keahlian dan materi pendidikan. Oleh karena itu, salah satu cara terbaik untuk menyebarluaskan program kesadaran risiko bencana adalah dengan mengintegrasikan inisiatif ini ke dalam kegiatan anak-anak melalui pendidikan. Informasi penting bagi sebagian besar penduduk dapat disampaikan melalui pengetahuan, keterampilan dan motivasi yang antusias dari anak-anak. Tujuan dari penelitian ini adalah untuk memberikan gambaran pendidikan kepada masyarakat luas tentang pentingnya pendidikan mitigasi bencana yang diinternalisasikan melalui pendidikan khususnya pembelajaran IPS bagi anak sekolah dasar. Anak-anak sebagai aset dan pemimpin masa depan, dapat belajar untuk melindungi diri mereka sendiri dan lingkungan mereka di masa depan melalui budaya mitigasi global untuk meningkatkan keselamatan diri mereka sendiri, keluarga mereka dan komunitas mereka saat mereka tumbuh dewasa. Anak-anak dipandang sebagai 'kekuatan besar' dalam perubahan perilaku bagi generasi berikutnya untuk menghadapi keadaan darurat ketika terjadi dan bangkit kembali dari dampak bencana.